The Relationship between a Country's Level of Tourism and Environmental Performance. (February 2020) - Bojanic, David C.; Warnick, Rodney B.
The tourism industry has come under scrutiny as a human activity that contributes to the increase in greenhouse gas (GHG) emissions. While tourism certainly contributes to GHG emissions, it would be interesting to know if the level of tourism has an effect on environmental performance. The purpose of this paper is to examine the impact of the level of tourism on GHG emissions on a global level using WDI panel data from 1995 to 2016. The findings indicate that the level of tourism does have an impact on GHG emissions. There is evidence that countries that rely more heavily on tourism as a percentage of GDP, have more tourism arrivals, and have higher tourism density actually have lower amounts of GHG emissions and better environmental performance.